Assessing the Impact of Autonomy on Job Satisfaction among Critical Care Nurses - Afifa, Amna; Aftab, Sadaqat; Mukhtar, Madiha; Ahmed, Sheharyar (Indus Journal of Bioscience Research, 2025)
Background: Job autonomy and job satisfaction are critical factors influencing the well-being and performance of nurses in critical care settings. Autonomy empowers nurses to make independent decisions, while job satisfaction enhances their motivation and commitment. This study aimed to assess the relationship between job autonomy and job satisfaction among critical care nurses at the University of Lahore Teaching Hospital. Methods: A quantitative, descriptive cross-sectional design was adopted. Data were collected from 36 critical care nurses using a structured questionnaire comprising job autonomy and job satisfaction scales. Demographic characteristics were analyzed using descriptive statistics. Results: The majority of participants were female (77.8%) and aged between 21–25 years (88.9%), with 2–4 years of experience (47.2%). Most respondents reported moderate levels of autonomy (55.6%) and job satisfaction (61.1%), with smaller proportions reporting low or good levels. Conclusion: This study highlights the importance of autonomy as a key predicator of job satisfaction among critical care nurses. Empowering nurses through participatory decision-making, resource availability, and supportive leadership can enhance both autonomy and satisfaction. Interventions targeting these areas could improve nurse retention and patient outcomes. Future research should explore these relationships in larger and more diverse populations to further validate these findings.